2007
DOI: 10.1002/glia.20546
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes—Friends or foes in multiple sclerosis?

Abstract: In multiple sclerosis (MS), the presence of demyelinating plaques has concentrated researchers' minds on the role of the oligodendrocyte in its pathophysiology. Recently, with the rediscovery of early and widespread loss of axons in the disease, new emphasis has been put on the role of axons and axon-oligodendrocyte interactions in MS. Despite the fact that, in 1904, Müller claimed that MS was a disease of astrocytes, more recently, astrocytes have taken a back seat, except as the cells that form the final gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
216
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(227 citation statements)
references
References 205 publications
4
216
0
5
Order By: Relevance
“…The radiologically normal WM surrounding these lesions is pathologically abnormal (Allen et al, 2001), and it is likely that identifying gene expression changes in astrocytes in the NAWM in MS may identify whether astrocytes contribute to, or prevent lesion initiation and progression. Several papers have discussed the complexity of astrocytes in MS, with emphasis on their dual function: on the one hand astrocytes are neurotoxic, through a deleterious immune response, increasing BBB permeability and inhibiting remyelination; whilst on the other these glial cells are neuroprotective, supporting oligodendrocyte remyelination and axonal regeneration (Williams et al, 2007, Nair et al, 2008, Brosnan and Raine, 2013. To date five studies have performed RNA profiling of the NAWM in MS compared to control WM, one recent study characterising the microRNA profile (Guerau-de-Arellano et al, 2015) and four studies have reported mRNA expression changes (Graumann et al, 2003, Lindberg et al, 2004, Zeis et al, 2008, Mycko et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The radiologically normal WM surrounding these lesions is pathologically abnormal (Allen et al, 2001), and it is likely that identifying gene expression changes in astrocytes in the NAWM in MS may identify whether astrocytes contribute to, or prevent lesion initiation and progression. Several papers have discussed the complexity of astrocytes in MS, with emphasis on their dual function: on the one hand astrocytes are neurotoxic, through a deleterious immune response, increasing BBB permeability and inhibiting remyelination; whilst on the other these glial cells are neuroprotective, supporting oligodendrocyte remyelination and axonal regeneration (Williams et al, 2007, Nair et al, 2008, Brosnan and Raine, 2013. To date five studies have performed RNA profiling of the NAWM in MS compared to control WM, one recent study characterising the microRNA profile (Guerau-de-Arellano et al, 2015) and four studies have reported mRNA expression changes (Graumann et al, 2003, Lindberg et al, 2004, Zeis et al, 2008, Mycko et al, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have opened up a new area of research to dissect the mechanism of Wnt signaling in OPC differentiation. But more importantly, given the growing interest to develop pharmacological inhibitors against the Wnt pathway in cancer therapy [59], it might be possible in the near future to use Wnt inhibitors to stimulate OPC differentiation and improve CNS remyelination in MS. One of the potential contributors of remyelination efficiency in MS is thought to be reactive astrocytosis in lesions, which can potentially have both beneficial and detrimental roles [60,61]. In search of putative astrocytic inhibitors of remyelination, a microarray analysis was performed on purified human astrocytes treated with cytokines that are known to be significantly upregulated in the brains of MS patients [62].…”
Section: Wnt Signalingmentioning
confidence: 99%
“…Therefore, gliotoxin models circumvent the autoimmune complexity and provide a reproducible demyelination episode to simplify analysis of cellular responses associated with remyelination. The mechanism of each toxin must be considered since this influences the stage of oligodendrocyte lineage cell involved (see below) and the effect on astrocytes, which contribute to the environmental signaling interactions regulating OP responses [8,9].…”
Section: Necessity For Different Models Of Experimental Demyelinationmentioning
confidence: 99%